Do urban tourists prefer vegetarianism? An urban-rural comparison of vegetarian consumption in China - Chen, Guoyi; Tan, Wei; Ran, Ning; Zhang, Jiansheng; Yan, Bangquan (Frontiers in Nutrition, 2022)
The adoption of a vegetarian diet might have public, health, and environmental benefits, however, still little is known about urban and rural Generation Z tourists’ attitude toward vegetarianism or vegetarian consumption under Chinese urban-rural dual structure settings. Hence, in order to address this gap, the present study adopted a sequential and mixed research approach based on a survey(n=212) and laddering interviews(n=20) to validate post-millennial tourists' motives for adopting a vegetarian diet. The results identified top four motives: environmental protection and resource conservation, ethical consideration, personal taste and choice and personal healthcare issue. The top four barriers to vegetarianism were unavailability and limited choice, peer pressure, traditional prejudice/habit and inability to change. Results also demonstrated that both rural and urban tourists adopt vegetarian consumption mainly for environmental protection and ethical consideration, a subtle difference between them lies in that urban vegetarian emphasis more on the benefits of ethical consideration, while rural ones emphasized on food and taste variety. Besides urban consumers consider unavailability and limited choice as the 1st barrier, while rural ones view traditional prejudice as the key barrier. Due to the pressure of traditional dietary habit and peer influence, rural tourists face much more challenges while adopting a vegetarian diet. Understanding the perceived benefits and barriers to consuming vegetarian in different regions will not only enrich the theory of food nutrition, but also expand Generation Z tourists' consumption behavior and practices.